THU0645 Impact of second-line therapy with abatacept versus other targeted dmards on the risk for infection-related hospitalizations and associated costs among ra patients in the united states. (12th June 2018) - Paul, D.; McDonald, L.; Marshall, A.; Curtice, T.; Lingohr-Smith, M.; Menges, B.; Lin, J.
Abstract : Background: Abatacept is a targeted DMARD (tDMARD) with a unique mechanism of action that has demonstrated a lower risk of infection-related hospitalizations as a second-line (2L) therapy compared with other tDMARDs among patients (pts) with RA. The cost savings in the United States associated with this reduced risk of infection-related hospitalizations is not well understood. Objectives: To compare infection-related hospitalisation risk and associated healthcare costs of RA pts who were treated at 2L with abatacept versus other tDMARDs, including TNF-α inhibitors (TNFis) and non-TNFis. Methods: Pts prescribed a 2L tDMARD (index date) who had ≥1 inpatient diagnosis or ≥2 outpatient diagnoses of RA in the 12 months prior to the index date were identified from the MarketScan ® Commercial and Medicare claims databases between 1 January 2010 and 30 September 2015. Pts were required to have 12 months of continuous insurance coverage prior to the index date (baseline period) and throughout the follow-up period (≥12 and up to 36 months). All pts were treated with a TNFi in first line. Infection-related hospitalizations and associated costs (on a per-pt per-month [PPPM] basis) were evaluated during baseline and follow-up periods. Multivariable regression analyses were used to evaluate the impact of index drugs on the risk of infection-related hospitalisation, as well as infection-related medical cost change from baseline to follow-up periods, while controlling for differences in baseline pt characteristics. Results: Among the study population, 285 pts (mean age 55 years; 85% female) were treated with abatacept, 954 with TNFis (mean age 52 years; 82% female) and 288 with non-TNFis (mean age 55 years; 76% female). After controlling for differences in pts' characteristics, Cox regression showed that the risk for an infection-related hospitalisation was significantly greater among those treated with TNFis (hazard ratio [HR] 2.8; 95% CI 1.2, 6.7; p=0.02) and higher, although not significant, among those treated with other non-TNFis (HR 2.4; 95% CI 0.9, 6.3; p=0.08) compared with those treated with abatacept. Infection-related medical costs were lower for abatacept compared with other non-TNFis as shown in the table 1. Conclusions: In the real-world setting in the United States, pts treated with abatacept versus other tDMARDs tended to have a lower risk for infection-related hospitalisation and lower infection-related medical costs. Disclosure of Interest: D. Paul Employee of: Bristol-Myers Squibb, L. McDonald Employee of: Bristol-Myers Squibb, A. Marshall Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, T. Curtice Employee of: Bristol-Myers Squibb, M. Lingohr-Smith Grant/research support from: Bristol-Myers Squibb, Employee of: Novosys Health, B. Menges Grant/research support from: Bristol-Myers Squibb, Employee of: Novosys Health, J. Lin Grant/research support from: Bristol-Myers Squibb, Employee of: Novosys Health